ANALISIS GEOMETRIK JALAN PADA ENAM RUAS JALAN TOL DALAM KOTA JAKARTA SEKSI A KELAPA GADING – PULO GEBANG - Achmad Pahrul Rodji; Indriasari; Deby Marc Handoyo (Jurnal Sipil Krisna, 2023)
In terms of transportation, the service of toll road infrastructure is the main factor that must be considered, so it must meet the road geometric technical requirements, so that toll road users are safe and comfortable driving. The influence of centrifugal force that occurs in corners often results in less safety and comfort for toll road users, both drivers and passengers. The object of research is the Six Sections of the Jakarta City Inner Toll Road Section A, the Kelapa Gading – Pulo Gebang section because it is one of the toll roads that has good road geometry for horizontal and vertical alignments. The purpose of this study is to analyze the road geometry on the Six Sections of the Jakarta City Inner Toll Road Section A Kelapa Gading – Pulo Gebang Sta 24+850 – Sta 25+350. The method uses field research methods, analyzes and evaluates the data based on the 2009 Bina Marga. Data analysis is to determine the geometric design of a comfortable and safe toll road. The results showed that the results of the 2009 Bina Marga calculation analysis, obtained a design speed of 77 km/hour with R = 231 m and Ts = 287.51 m, while the actual field speed with a design speed of 77 km/hour R = 233.50 m and Ts = 247 m. So there are differences in the values of R and Ts due to limited land in the field and the maximum speed set is 70 km/hour. In this condition, the geometric design of the road must be in accordance with the conditions of the land in the field and conduct a preliminary survey using the Theodolit Station measuring instrument in order to obtain elevation data for different heights and contour conditions in the area to be built for a road.